2019
DOI: 10.3390/w12010122
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Occurrence of Phthalate Esters in Beach Seawater in the Southeast Coast Region, South Korea

Abstract: In modern times, humans have contributed to the occurrence of phthalate esters (PEs) in various environmental matrices by consuming plastics that generally contain PEs, which are essential synthetic organic chemicals for fabrication of various consumer products. Five beaches in Ulsan and Busan, South Korea, were investigated for the anthropogenic occurrence of four PEs (dimethyl phthalate (DMP), diethyl phthalate (DEP), di-n-butyl phthalate (DnBP), and bis(2-ethylhexyl) phthalate (DEHP)) in beach seawater. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 29 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Their effect on the human organism is mainly connected with their content in food products and cosmetic goods. A wide application of PEs in industry resulted in significant contamination of soil and inland water bodies in the countries of Europe and Asia as well as seas, and this allows the revision of the existing notion about the levels of PEs impact [82][83][84][85]. These substances are referred to the compounds with estrogen-like effect due to binding to estrogen receptors, they also are capable of competing with androgens for binding to a receptor [86].…”
Section: Reviewsmentioning
confidence: 99%
“…Their effect on the human organism is mainly connected with their content in food products and cosmetic goods. A wide application of PEs in industry resulted in significant contamination of soil and inland water bodies in the countries of Europe and Asia as well as seas, and this allows the revision of the existing notion about the levels of PEs impact [82][83][84][85]. These substances are referred to the compounds with estrogen-like effect due to binding to estrogen receptors, they also are capable of competing with androgens for binding to a receptor [86].…”
Section: Reviewsmentioning
confidence: 99%
“…Several conclusions have been made by different authors regarding the effect of seasonal effects on pollutant concentration in surface waters. For example, the study of Heo et al (2020) indicated that rainfall events typically dilute PAE concentrations in the seawater of the beaches. Huang et al (2015) reported that the effect of rainfall on the PAH concentrations in the Pearl River Estuary was insignificant due to the different contamination sources for these types of pollutants.…”
Section: Organic Pollutant Groups In Liffey River On the Four Sampling Daysmentioning
confidence: 99%
“…It has been concluded that the input of contaminants into the surface water environment depends on the physicochemical characteristics of the environment (soils, pH, rainfall level) and each pollutants' respective properties. Therefore, it is difficult to generalise about the conclusions (Heo 2020;Moreno-González et al 2013a;Moreno-González et al 2013b).…”
Section: Organic Pollutant Groups In Liffey River On the Four Sampling Daysmentioning
confidence: 99%
“…Owing to their growing economic and commercial interest, PEs are by far the most used synthetic organic chemicals in a large variety of products since 1930s (Wang et al, 2018;Heo et al, 2020). Global production of PEs is estimated at 6 to 8 million tons per annum (Seyoum and Pradhan, 2019) with utilization by various industrial companies sitting at more than 3 million tons (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Global production of PEs is estimated at 6 to 8 million tons per annum (Seyoum and Pradhan, 2019) with utilization by various industrial companies sitting at more than 3 million tons (Zhang et al, 2021). These compounds are mainly used for enteric coatings of nutritional supplements and pharmaceutical pills, as viscosity controlling agents, emulsifying agents, lubricants, binders, gelling agents, stabilizers film formers, dispersants, and suspending agents but primarily as plasticizers (Ji et al, 2014;Wang B. et al, 2015;Wang et al, 2018;Heo et al, 2020;USEPA, 2021). They are generally added to plastic materials such as polyethylene, polyethylene terephthalate, polyvinyl acetate and polyvinyl chloride (PVC), at the composition of up to 60% by weight of the PEs, to improve the elasticity and extensibility of the polymers (Giuliani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%